Representasi Perempuan dalam Media di Indonesia - Danang Trijayanto (Ultimacomm: Jurnal Ilmu Komunikasi, 2017)
Women in the media become one of the objects of media culture. The meaning of women is visualized through various commodities of media industry products, such as films, video clips, and television commercials. Data of popular culture in cultural studies show women are often positioned lower than men in a patriarchal culture. This study discusses how women are marginalized in three pop music clips entitled 'terlalu cinta’, 'puisi' and 'merindunya'. The method used in this study is critical discourse analysis using critical semiotics. Images and other visual elements were used to examine the portrayal of women in Indonesia’s social structure. In the media culture especially, in the popular music video clips in Indonesia, there are several meanings emerged, such as women need men in terms of daily activities and in terms of sexual needs. The room setting in the video clip indicates that the woman desperately needs a man for her biological needs. The other portrayal shows women need men for social status. The room setting and the male partner shows a picture of a need for an established social status. Men who look neat and situated in a luxurious environment symbolizes his part of the upper class members. Women are also figured as the ones who rely on men. Keywords: representation, women, media, discourse, critical